DIMENSI NILAI-NILAI KETELADANAN DALAM BUKU AJAR AQIDAH AKHLAK KELAS VII MADRASAH TSANAWIYAH - Ruhana Ruhana (Koordinator Perguruan Tinggi Agama Islam (KOPERTAIS) Wilayah V Aceh, 2022)
Exemplary is an important aspect of the learning process that takes place in various educational institutions. Exemplary behavior is essential for knowledge transmission to transform into student character. However, exemplary behavior often goes unnoticed, especially in taking its value from the learning material that is taught in class. Therefore, this article aims to briefly map the dimensions of exemplary values contained in student textbooks for the Aqidah Akhlak Madrasah Tsanawiyah subject. The method used in this article is the literature review method. The book that is the main source of this study is the Textbook for Class VII Students of Madrasah Tsanawiyah, written by Akhmad Fauzi and published by the Ministry of Religion of the Republic of Indonesia. Based on the literature review conducted, this study found that there are at least several dimensions of exemplary values that can be used as references by teachers when carrying out their duties in the learning process. The dimensions of the exemplary value are: 1) always speaking the truth; 2) always being ready to have a dialogue with anyone; 3) always showing gratitude; 4) being humble; 5) always showing affection; and 6) always prioritizing deliberation in every decision. The six moral values can be implemented by the teacher when carrying out teaching and learning activities by first setting an example in each of his actions. The teacher's example is significant because, after all, exemplary behavior cannot be spoken but must be seen in action to be fully appreciated.AbstrakKeteladanan merupakan salah satu aspek penting dalam proses pembelajaran yang berlangsung di berbagai lembaga pendidikan. Keteladanan adalah kunci agar transmisi pengetahuan yang dilakukan dapat berubah menjadi karakter siswa. Namun, keteladanan seringkali gagal diketahui dan refleksi dari materi pembelajaran yang diajarkan di dalam kelas. Oleh sebab itu, artikel ini bertujuan untuk memetakan secara ringkas tentang dimensi nilai-nilai keteladanan yang terkandung dalam buku ajar siswa mata pelajaran Aqidah Akhlak Madrasah Tsanawiyah. Metode yang digunakan dalam artikel ini adalah metode kajian kepustakaan. Buku yang menjadi sumber utama kajian ini adalah Buku Ajar Siswa Kelas VII Madrasah Tsanawiyah yang ditulis oleh Akhmad Fauzi dan diterbitkan oleh Kementerian Agama Republik Indonesia. Berdasarkan kajian literatur yang dilakukan, artikel ini menemukan setidaknya terdapat beberapa dimensi nilai keteladanan yang dapat dijadikan rujukan oleh guru ketika menjalankan tugasnya dalam proses pembelajaran. Dimensi nilai keteladanan tersebut adalah 1) senantiasa berkata yang benar/jujur; 2) bersedia untuk selalu berdialog dengan siapa pun; 3) selalu menunjukkan rasa syukur; 4) bersikap rendah hati; 5) selalu menampilkan sikap kasih sayang; dan 6) selalu mendahulukan musyawarah dalam setiap keputusan. Keenam nilai moral tersebut dapat diimplementasikan oleh guru ketika sendang melaksanakan kegiatan belajar mengajar dengan terlebih dahulu mencontohkan dalam setiap tundakannya. Contoh dari guru menjadi penting karena bagaimanapun keteladanan tidak bisa hanya diucapkan tetapi harus diimplementasikan agar dapat dilihat bentuk nyatanya.